2007
DOI: 10.1158/0008-5472.can-06-4487
|View full text |Cite
|
Sign up to set email alerts
|

ERM/ETV5 Up-regulation Plays a Role during Myometrial Infiltration through Matrix Metalloproteinase-2 Activation in Endometrial Cancer

Abstract: We have described recently the Ets family transcription factor, ERM/ETV5, specifically up-regulated in endometrioid endometrial carcinoma (EEC) and associated with myometrial infiltration. Ets family members have been correlated to tumor progression by up-regulating the expression of matrixdegrading proteases. In the present study, we investigated the possibility that in EEC, ERM/ETV5 may act by inducing the expression of genes involved in extracellular matrix remodeling. Unraveling the molecular events associ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
73
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 28 publications
6
73
0
Order By: Relevance
“…35 Interestingly, we have previously described the Ets family member ERM/ETV5, specifically upregulated in endometrial cancer associated with an initial switch to myometrial infiltration, acting through MMP-2 gelatinolytic activity to confer invasive capabilities. 6,7,36 Further work must be performed to fully characterize the mechanisms underlying the promotion of distant metastasis by RUNX1 modulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35 Interestingly, we have previously described the Ets family member ERM/ETV5, specifically upregulated in endometrial cancer associated with an initial switch to myometrial infiltration, acting through MMP-2 gelatinolytic activity to confer invasive capabilities. 6,7,36 Further work must be performed to fully characterize the mechanisms underlying the promotion of distant metastasis by RUNX1 modulation.…”
Section: Discussionmentioning
confidence: 99%
“…7 pEGFP-C2 vector was purchased from BD Biosciences (Franklin Lakes, NJ). Plasmid construction consisted of the full-length human RUNX1 being removed with EcoRI from a pSV-hRUNX1 construct; it was then inserted at the EcoRI position at the multiple cloning site of the pEGFP-C2 vector.…”
Section: Cell Lines Constructs and Stable Transfectionmentioning
confidence: 99%
See 1 more Smart Citation
“…HEC-1A endometrial carcinoma cells were cultured as described (14), and RL95-2 endometrial adenosquamous carcinoma cells were grown in DMEM/F12 medium containing 10% FBS and 1% penicillin/streptomycin. The invasion assay was conducted as described (15).…”
Section: Cell-inverted Invasion Assaymentioning
confidence: 99%
“…30,31 Moreover, Erm overexpression enhances the aggressiveness of cancer cells in vitro and correlates with disease progression in endometrial carcinoma. [32][33][34] To the best of our knowledge, the roles of Pea3 group transcription factors in ESCC have not been studied. In the present study, we investigated the expression of the three transcription factors in an ESCC patient cohort and found that Pea3 overexpression was associated with poor prognosis.…”
mentioning
confidence: 99%